2023
DOI: 10.3390/foods12142645
|View full text |Cite
|
Sign up to set email alerts
|

Cultured Meat Safety Research Priorities: Regulatory and Governmental Perspectives

Abstract: As with every new technology, safety demonstration is a critical component of bringing products to market and gaining public acceptance for cultured meat and seafood. This manuscript develops research priorities from the findings of a series of interviews and workshops with governmental scientists and regulators from food safety agencies in fifteen jurisdictions globally. The interviews and workshops aimed to identify the key safety questions and priority areas of research. Participants raised questions about … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 90 publications
0
0
0
Order By: Relevance
“…Maintaining the storage stability of cultured meat serves not only the purpose of protecting consumers’ health from microorganisms but also aims to prevent changes in the texture characteristics of the final product, which could impact the tissue structure ( Rubio et al, 2020 ). Ong et al (2023) reported that the microbial composition of the final product is influenced by the indigenous microbial population in the production environment. Therefore, the post-production microbial composition of cultured meat is anticipated to be similar to that of the indigenous microbial population in the production environment.…”
Section: Quality Properties Of Cultured Meatmentioning
confidence: 99%
“…Maintaining the storage stability of cultured meat serves not only the purpose of protecting consumers’ health from microorganisms but also aims to prevent changes in the texture characteristics of the final product, which could impact the tissue structure ( Rubio et al, 2020 ). Ong et al (2023) reported that the microbial composition of the final product is influenced by the indigenous microbial population in the production environment. Therefore, the post-production microbial composition of cultured meat is anticipated to be similar to that of the indigenous microbial population in the production environment.…”
Section: Quality Properties Of Cultured Meatmentioning
confidence: 99%
“…During the last five years, several articles were published on regulatory frameworks of the cell-based meat. For example, researchers evaluated the food safety considerations and research priorities for cell-based meat [ 13 ], cell-based meat safety research priorities with an emphasis on regulatory and governmental perspectives [ 14 ], and policy frameworks, and regulation [ 11 ]. Food safety aspects of the cell-based meat have also been reviewed and developed [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%